Carbon‐Based Estimate of Nitrogen Fixation‐Derived Net Community Production in N‐Depleted Ocean Gyres. Issue 8 (27th August 2018) - Ko, Young Ho; Lee, Kitack; Takahashi, Taro; Karl, David M.; Kang, Sung‐Ho; Lee, Eunil
Abstract: Accurate estimation of net community production (NCP) in the ocean is important for determining the future trend for carbon dioxide concentrations in the atmosphere and thus for understanding the global carbon cycle and climate change. Most methods for measuring NCP rely on analysis of dissolved fixed inorganic nitrogen species (N), which are believed to be limiting factors for NCP. However, in the vast areas of the ocean gyres only low levels of N are available for phytoplankton during much of the year. In this study the NCP was estimated by summing the seasonal reduction in the concentration of dissolved inorganic carbon (CT ) in the surface mixed layer, corrected for changes associated with salinity variation, net air‐sea CO2 flux, horizontal C advection, non‐Redfield diffusive C and N fluxes (deviations from the C:N ratio of 7), and anthropogenic nitrogen deposition. The mixed layer reduction in CT was calculated from an annual CT cycle, deduced from comprehensive records of surface pCO2 and total alkalinity, using an established thermodynamic model. This method yielded a value of 0.6 ± 0.2 Pg of C, which represents the NCP that occurred during the warming period (approximately 8 months) in the nitrate‐depleted (<0.2 μmol/kg) ocean. Our estimate is broadly consistent with the global N2 fixation rate estimated using the 15 N‐based method and suggests that N2 fixation by microorganisms is a major driver for this NCP. Key Points: We estimated net community production (NCP) by summing the mixed layer reduction in dissolved inorganic carbon in N‐depleted ocean gyres The mixed layer CT reduction was calculated from an annual CT cycle, deduced from global records of surface pCO2 and total alkalinity Our study suggests that N2 fixation by microorganisms is a major driver for this NCP in the vast areas of ocean gyres